Geochemical characteristics of the infilling of ground wedges at Puerto Deseado (Santa Cruz, Argentina): palaeoenvironmental and chronological implications - Zanchetta, Giovanni (2018)
Ground wedge structures of cryogenic origin are common in the Quaternary sediments along the coast of the Patagonia, and their formation is related to climatic cold events experienced by this area in the Late Quaternary. The infilling sediments of two wedges generations were analyzed in the area of Puerto Deseado. Bulk chemistry (major elements), X-ray diffraction (XRD), morphoscopic observations with Scanning Electronic Microscope (SEM) and chemical analyses of volcanic glass shards were undertaken to provide indications about infilling sediment provenience, along with chronological constraint for wedge formation. Bulk chemistry and XRD patterns indicate a significant SiO2- enriched composition of the sediment infilling compared to the most of the loess deposits of the North Argentina and the present day dust originated in Patagonia. This was interpreted as due to the nature of the bedrock present over the Deseado Massif. SEM morphoscopic characteristics of glass shards evidence typical aeolian reworking features, with impact structures and indented edges of the volcanic fragments. Chemical analyses of the glass shards indicate that they were probably generated by the H0 eruption (17,300-17,400 cal yr BP) of the Hudson volcano. Volcanological data indicate that H0 eruption dispersed toward NE, but volcanic glasses were available for reworking due to a WNW component in the western wind direction. Over the Deseado Massif structural high the glass shards mixed with sediments enriched in SiO2, and were eventually deflated further to SE reaching the present coastal area and infilling the frost cracks. The age of the glass shards (17,300-17,400 cal yr BP) and that of the sandy layer affected by cryogenic structures (14,670±750 yr BP) well constrain to the Late Glacial both wedge generations.